2020
DOI: 10.4085/1062-6050-0190.20
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Pain in Patellofemoral Pain: A Systematic Review and Meta-Analysis Examining Signs of Central Sensitization

Abstract: Objective: Patellofemoral pain has high recurrence rates and minimal long-term treatment success. Central sensitization refers to dysfunctional pain modulation that occurs when nociceptive neurons become hyper responsive. Research in this area in PFP has been increasingly productive in the past decade. The aim of this review is to determine whether evidence supports manifestations of central sensitization in individuals with PFP. Data sources: MeSH terms for quantitative sensory testing (QST)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…The somewhat modest improvements seen in our and other recent studies on exercises for PFP raise the question if treatment plans focusing on strengthening and biomechanically informed movement quality alone address the right components contributing to the pain experience. Growing evidence suggests that psychological features may play a role in long-standing PFP 52–54. Future studies should aim at identifying possible patient characteristics that predict successful outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The somewhat modest improvements seen in our and other recent studies on exercises for PFP raise the question if treatment plans focusing on strengthening and biomechanically informed movement quality alone address the right components contributing to the pain experience. Growing evidence suggests that psychological features may play a role in long-standing PFP 52–54. Future studies should aim at identifying possible patient characteristics that predict successful outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Another way to assess the existence of CS is through Quantitative Sensory Testing (QST), which are a battery of tests that assesses pain threshold (pressure, heat or electrical stimuli), temporal pain summation phenomenon (changes in pain perception over time during a sustained or repeated stimulus) and conditioned pain modulation (pain from a noxious stimulus is decreased by a second noxious stimulus). A systematic review of studies evaluating the presence of CS using QST in AKP patients found that signs of CS were present in some patients, indicating altered pain modulation [33]. Unlike QST, which assesses sensory system responses to sensory stimuli, CSI primarily assesses symptoms related to CS.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, altered central and peripheral pathways could be related to long lasting effects of interventions for PFPS. Because of the chronic character of PFPS, pain modulation mechanisms may deserve more attention in the treatment of patellofemoral pain (Bartholomew et al, 2019;Sigmund et al, 2020).…”
Section: Discussionmentioning
confidence: 99%